Agency contract and arbitration: order of the Court of Appeal of Barcelona number 116/2018 of 17th May - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Opposing the idea of building an exclusive jurisdiction forum based on the rules of the Law on agency contract, the Court of Appeal of Barcelona insists on their purely internal scope, limited to the discipline of venue, as well as as the ability of the parties to dispose of the matter, thus excluding any intent to restrict their freedom.